Introduction: A Meeting with Bedřich Loewenstein - Hermann, Tomáš (Dějiny – teorie – kritika, 2009)
To mark the eightieth birthday of Professor Bedřich Loewenstein (on 20 June 1929) a workshop was held in Prague on 8 June 2009, on the topic ‘The History of Faith in Progress’. At the workshop, Loewenstein’s most recent large book, Víra v pokrok: Dějiny jedné evropské ideje (Faith in Progress: A History of One European Idea, Prague 2009; originally published as Der Fortschrittsglaube: Geschichte einer europaischen Idee, Gottingen 2008), was comprehensively discussed, with the author in attendance. In addition to Loewenstein’s autobiographical contribution, the following eight articles are reflections on Loewenstein’s book and his life’s work as an historian.